2022
DOI: 10.1080/21655979.2021.2019874
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of hypoxia-inducible factor 1-alpha (HIF1α) interferes with angiopoietin-like protein 2 (ANGPTL2) to attenuate high glucose-triggered hypoxia/reoxygenation injury in cardiomyocytes

Abstract: To investigate the role of hypoxia-inducible factor 1-alpha (HIF1A) in hypoxia/reoxygenation (H/R) injury of cardiomyocytes induced by high glucose (HG). The in vitro model of coronary heart disease with diabetes was that H9c2 cells were stimulated by H/R and HG. Quantitative reverse transcription PCR (RT-qPCR) and Western blot analysis were used to detect the expression of HIF1A and angiopoietin-like protein 2 (ANGPTL2) in H9c2 cells. Cell viability and apoptosis were, respectively, estimated by Cell Counting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“… 71 Interestingly, increased levels of ANGPTL2 may also serve as an indicator of increased hypoxic inducible factor 1-α signalling. 62 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 71 Interestingly, increased levels of ANGPTL2 may also serve as an indicator of increased hypoxic inducible factor 1-α signalling. 62 …”
Section: Discussionmentioning
confidence: 99%
“…71 Interestingly, increased levels of ANGPTL2 may also serve as an indicator of increased hypoxic inducible factor 1-α signalling. 62 Three prior studies have reported the results of proteomics analyses before and after SGLT2 inhibition, but the three studies each evaluated fewer than 80 patients, <10% of the patients in the current EMPEROR proteomics substudy. 63,72,73 Of the three, the study most comparable to our analyses was carried out by Ferrannini et al, 63 although that study differed from ours in several important respects.…”
Section: Discussionmentioning
confidence: 99%
“…These viewpoints align precisely with the results of our bioinformatics analysis. It’s worth noting that there is still a debate over the primary mechanism of “autophagic cell death”, whether it involves excessive mitophagy or the extensive accumulation of autophagosomes [ 65 ]. A new consensus is emerging that the changes induced by cellular damage align with the formation and initiation of autophagosomes in myocardial cells, contributing to the process of cell death [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vector was transfected in cells stably transfected with si-SP1. After 48 h, the luciferase activity was determined using the dual luciferase reporter system (Promega) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%